2017
DOI: 10.1007/s10792-017-0765-2
|View full text |Cite
|
Sign up to set email alerts
|

On the regional variability of averaged cell area estimates for the human corneal endothelium in relation to the extent of polymegethism

Abstract: Purpose To assess variability in the coefficient of variation (COV) in cell area estimates when using different numbers of cells for endothelial morphometry. Methods Using non-contact specular microscopy images of the corneal endothelium, 4 sets of 20 cases were selected that included 200 cells and had overall (global) COV values of less than 30 (group 1), 31-40 (group 2), 41-50 (group 3) and over 50% (group 4). Subjects could be normal, or had ophthalmic disease (such as diabetes), a history of rigid or soft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Neither in this study nor in our previous study [14] have we found significant COV increases after surgery, in accordance with the results of other authors [10,11]. Thus, the COV is not a very good indicator of corneal endothelial cell loss and this has been also suggested by other authors [31,32].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Neither in this study nor in our previous study [14] have we found significant COV increases after surgery, in accordance with the results of other authors [10,11]. Thus, the COV is not a very good indicator of corneal endothelial cell loss and this has been also suggested by other authors [31,32].…”
Section: Discussionsupporting
confidence: 90%
“…The baseline COV were similar in the one-step and two-step groups, also similar to those found in our previous study [ 14 ] and did not decrease significantly after phacotrabeculectomy. Most studies have documented COV between 30 and 40%, but also values of up to 60% [ 3 , 10 , 14 , 31 ], and increasing values when there is endothelial loss [ 10 , 11 , 14 , 18 , 32 ]. Neither in this study nor in our previous study [ 14 ] have we found significant COV increases after surgery, in accordance with the results of other authors [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial efficiency can be evaluated from values such as mean cell area, cell density, CV and percentage of hexagonal cells. In such manner, it is possible to evaluate endothelial pleomorphism and polymegathism as a marker of past or present endothelial damage or disease (Doughty, 2006(Doughty, , 2018Doughty & Oblak, 2008). Different methods are used, such as specular microscopy, confocal microscopy and SEM.…”
Section: F I G U R E 3 Scanning Electron Micrograph Of Normal Corneal...mentioning
confidence: 99%
“…Different methods are used, such as specular microscopy, confocal microscopy and SEM. The latter not only provides information on cell morphology, but is high enough to evaluate the three-dimensional cell organization and the ultrastructure of endothelial cells (Coyo et al, 2019;Doughty, 1989Doughty, , 2018Meek & Fullwood, 2001;Tamayo-Arango et al, 2009). The downside is that significant cellular contraction occurs with processing by dehydration with glutaraldehyde.…”
Section: F I G U R E 3 Scanning Electron Micrograph Of Normal Corneal...mentioning
confidence: 99%